Analytical hybrid redundancy system for the fault tolerance of advanced driver assistance systems. (October 2017) - Lee, Sanghyeop; Lee, Suk; Lee, Kyung-Chang; Kim, Man-Ho
The growing dependence on electronic sensors has resulted in increased concerns over the fault tolerance in safety-critical systems. For example, a vehicle with an advanced driver assistance system, which assists safe driving using numerous electronic elements, should be fault tolerant because sensor failures can lead to events in which car occupants receive serious injuries. However, it is often undesirable to have multiple redundant sensors because of the high cost of critical sensors such as the radar in an advanced driver assistance system. To address this problem, we present an analytical hybrid redundancy system that provides fault tolerance using fault detection and exception-handling algorithms. On the basis of the actual range data from an advanced driver assistance system radar, we present the results of numerical simulations of the analytical hybrid redundancy system and show that it outperforms existing approaches with respect to a number of performance indices.